Sports injury prevention project: the netball performance test - McManus, Alexandra; Stevenson, M. (Curtin Health Innovation Research Institute, Curtin University, 2003)
These slides present the results of the research of Professor Alexandra McManus undertaken as part of her Ph.D. entitled 'Sports injury prevention in non-elite Australian football, field hockey and netball', University of Western Australia, 2003.